730. A Phase 3, Randomized, Double-Blind Study to Evaluate the Efficacy and Safety of Ridinilazole Compared with Vancomycin for the Treatment of Clostridioides difficile Infection. (15th December 2022) - Okhuysen, Pablo C; Ramesh, Mayur; Garey, Kevin W; Louie, Thomas J; Cisneros, Julian Torre; Stychneuskaya, Alena; Kiknadze, Nino; LI, Jianling; Duperchy, Esther; Wilcox, Professor Mark H; Montoya, Jose G; Styles, Lori; et al.
Abstract: Background: Vancomycin (VAN) therapy for C. difficile infection (CDI) is effective with > 80% clinical response (CR) but is associated with 20–30% recurrence rate (rCDI). Secondary bile acids (2° BAs) inhibit C. difficile germination and help prevent rCDI. VAN depletes the gut microbiome decreasing the conversion of primary bile acids to 2° BAs. Ridinilazole (RDZ) is a highly selective anti-CDI, DNA-binding antibiotic in development for the treatment of CDI and prevention of rCDI. Methods: A global, double-blinded, randomized Phase 3 trial assessed a 10-day treatment with RDZ 200 mg BID vs VAN 125 mg QID for CDI. The primary endpoint was sustained clinical response (SCR) defined as CR and no rCDI through 30 days post-end of treatment (EOT). Other endpoints included rCDI, microbiome diversity and composition, and microbiome-derived 2° BAs concentration. rCDI was defined as a new episode of diarrhea with confirmed positive free toxin test (FTT), requiring additional CDI therapy. All participants were monitored for treatment emergent adverse events (TEAE). Results: Of the 759 patients (pts) enrolled, 745 were included in the mITT population (RDZ n=370, VAN n=375). RDZ achieved a numerically higher SCR rate than VAN (73.0% vs 70.7%) p=0.4672. RDZ resulted in a significant reduction in rCDI rate (8.1% vs 17.3%, p=0.0002) (Fig 1). In a pre-specified subpopulation, this was most notable in pts not receiving other antibiotics (rCDI 6.7% in RDZ vs 16.5% in VAN, p=0.0005). Microbiome alpha diversity was higher for RDZ vs VAN at EOT and EOT+30d (p< 0.0001 and p≤ 0.0007 respectively, Fig 2) as were relative abundance (p< 0.0001 and p=0.0203 respectively), and concentrations of 2° BAs (Fig 3). Higher microbiome diversity and concentrations of 2° BAs at EOT were associated with both lower rCDI and higher SCR rates. RDZ was well tolerated (pts with ≥ 1 TEAE: RDZ 36.4% vs VAN 35.5%, treatment discontinuation due to TEAE: RDZ 0.8% vs. VAN 2.9%). Fig 1: Time to CDI Recurrence Fig 2: Alpha-Diversity and Relative Abundance of Phyla Fig 3: Fecal Secondary Bile Acid Concentration by Study Visit Conclusion: RDZ was effective for sustained clinical response and safe for the treatment of patients with CDI. This was most notable in pts not receiving antibiotics. Compared to VAN, RDZ patients had faster recovery of fecal 2° BA, consistent with the preservation of microbiome diversity, resulting in a significantly lower rate of rCDI. Disclosures: Pablo C. Okhuysen, MD, AstraZeneca: Stocks/Bonds|Beam Therapeutics: Stocks/Bonds|Biontech: Stocks/Bonds|Deinove: Grant/Research Support|Ferring: Advisor/Consultant|Glaxo Smith Kleine: Stocks/Bonds|Johnson and Johnson: Stocks/Bonds|Melinta: Grant/Research Support|Merck Sharp & Dohme Corp: Grant/Research Support|Moderna: Stocks/Bonds|Napo Pharmaceuticals: Advisor/Consultant|Napo Pharmaceuticals: Grant/Research Support|Novavax: Stocks/Bonds|Pfizer: Stocks/Bonds|Summit: Advisor/Consultant|Summit: Grant/Research Support Kevin W. Garey, PharmD, MS, Acurx: Grant/Research Support|cidara: Advisor/Consultant|cidara: Grant/Research Support|Paratek: Grant/Research Support|Seres Health: Grant/Research Support|Summit: Grant/Research Support Thomas J. Louie, MD, adiso therapeutics: Advisor/Consultant|adiso therapeutics: Grant/Research Support|crestone: Advisor/Consultant|crestone: Grant/Research Support|Finch: Advisor/Consultant|Finch: Grant/Research Support|Seres Therapeutics: Advisor/Consultant|Seres Therapeutics: Grant/Research Support|Seres Therapeutics: Honoraria|summit plc: Grant/Research Support|vedanta biosciences: Advisor/Consultant|vedanta biosciences: Grant/Research Support Jianling LI, MS, Abbott: Stocks/Bonds|Abbvie: Stocks/Bonds|ALX Oncology: Stocks/Bonds|BioNTech: Stocks/Bonds|Bluebird Bio: Stocks/Bonds|Cytokinetics: Stocks/Bonds|I-Mab: Stocks/Bonds|Johnson & Johnson: Stocks/Bonds|Moderna: Stocks/Bonds|TG Therapeutics: Stocks/Bonds Esther Duperchy, PhD, Summit Plc: Employee Jose G. Montoya, MD, Summit: Honoraria|Summit: Stocks/Bonds Lori Styles, MD, Abbvie: Stocks/Bonds|Summit Therapeutics: employee|Summit Therapeutics: Stocks/Bonds Fong Clow, Sc. D, Summit Therapeutics: Employee Danelle James, MD, Summit Therapeutics: Employee.